Eco-Driving for Energy Efficient Cornering of Electric Vehicles in Urban Scenarios. Issue 2 (2020) - Padilla, G.P.; Pelosi, C.; Beckers, C.J.J.; Donkers, M.C.F.
Abstract: In this paper, we propose a model for eco-driving that considers cornering effects. The proposed model purely relies on the geometric configuration of the vehicle and road. Consequently, we propose an eco-driving optimal control problem formulation that is suitable for both straight and curved trajectories in urban scenarios. Moreover, it can be applied for vehicles with front wheel drive (FWD) or rear wheel drive (RWD). We use a case study for an electric vehicle executing cornering maneuvers to validate the proposed approach with a high fidelity vehicle model. Results show an approximated improvement of 8% in energy savings with respect to traditional eco-driving strategies, especially in trajectories with large curvatures.